2020
DOI: 10.1111/faf.12495
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of genetic parameters of production traits in cultured shrimp species

Abstract: Genetic parameters of growth, reproductive efficiency and survival are important for designing successful genetic improvement programmes. In this study, a database was assembled and a meta-analysis was conducted using 87 peer-reviewed published studies on genetic parameters of 63 economically important traits reported across nine major farmed shrimp species. A total of 641 estimates of heritability, 978 estimates of genetic correlations and 658 estimates of phenotypic correlations were included in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 115 publications
2
7
0
Order By: Relevance
“…Heritability of growth traits were moderately high in this study (e.g., 0.27 ± 0.07 for body weight and 0.32 ± 0.08 for body length traits), suggesting selection for these traits will lead to significant response in breeding programs. This finding corroborates with the previous findings, where heritability for growth traits were moderate to high, ranging from 0.23 to 0.69 in P. monodon ( Hasan et al, 2020 ), indicating that these traits will be highly responsive during selection for genetic improvement. Of greater significance in this study is the impact of selection for growth on color traits.…”
Section: Discussionsupporting
confidence: 92%
“…Heritability of growth traits were moderately high in this study (e.g., 0.27 ± 0.07 for body weight and 0.32 ± 0.08 for body length traits), suggesting selection for these traits will lead to significant response in breeding programs. This finding corroborates with the previous findings, where heritability for growth traits were moderate to high, ranging from 0.23 to 0.69 in P. monodon ( Hasan et al, 2020 ), indicating that these traits will be highly responsive during selection for genetic improvement. Of greater significance in this study is the impact of selection for growth on color traits.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, moderate to high heritability estimates were recorded for BW (0.32 ± 0.05), BL (0.36 ± 0.06) and BS (0.32 ± 0.05), suggesting substantial potential for genetic improvement of these traits in the P. monodon population studied. All these are growth-related traits and these findings corroborate the previous findings of P. monodon genetic parameter estimates ( Kenway et al, 2006 ; Macbeth et al, 2007 ; Coman et al, 2010 ; Noble et al, 2020b ), although a meta-analysis conducted by Hasan et al (2020) reported the estimates ranged from 0.18 to 0.69. Similarly Noble et al (2020b) reported the heritability estimate of 0.38 for BW trait of P. monodon for a smaller subset of this population.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly Noble et al (2020b) reported the heritability estimate of 0.38 for BW trait of P. monodon for a smaller subset of this population. A higher heritability of 0.55 for growth rate (at 54 weeks) and 0.47 body weight were reported by Kenway et al (2006) and Van Sang et al (2020), respectively. However, Sun et al (2015) reported low heritability estimates for body length (0.18) and body weight (0.24) trait of this species.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations